Marked Improvement of Insulin Sensitivity Without Enhancement of GLP-1 and Insulin Secretion After Roux-en-Y Gastric Bypass Surgery in a Mildly Obese Patient with Diabetes - Yamashita, K.; Sato, Y.; Oki, K.; Kishimoto, H.; Yamauchi, K.; Aizawa, T. (Hormone and Metabolic Research, 2014)
Roux-en-Y gastric bypass is an option of treatment for morbidly obese patients with diabetes. However, the value of the operation in mildly obese patients is not established. We report the first prospective systematic endocrine and metabolic analysis in a mildly obese patient who underwent a Roux-en-Y gastric bypass. In a 49-year-old man with BMI 32.6 kg/m2 having type 2 diabetes, intramucosal gastric cancer was treated by partial gastrectomy with Roux-en-Y gastric bypass. Pre-operatively, he received 53 U/day insulin and the HbA1c value was 63 mmol/mol: meal tolerance test showed diabetic hyperglycemia and low insulin sensitivity with attenuated insulin secretion and normal glucagon-like peptide 1(7–36) secretion. After the operation, hypoglycemic agent was stopped. Body weight reduced from 84.0 to 77.0 kg within 2 weeks and increased thereafter to 79.4 kg at 4 months later, when the degree of hyperglycemia was unchanged as indexed by a HbA1c value of 62 mmol/mol. Upon repeated meal tolerance test, no increase of glucagon-like peptide 1 and insulin secretion, but significantly improved hepatic and peripheral insulin sensitivity were found, compared to the preoperative meal tolerance test. Marked dissociation of endocrine and metabolic effects of Roux-en-Y gastric bypass, that is, absence of increased glucagon-like peptide 1/insulin secretion with improvement of insulin sensitivity, was found in a mildly obese patient with type 2 diabetes.
Keywords: GLP-1; insulin; RYGB